Media Sosial Sebagai Alat Kampanye Pemilu 2024: Perspektif Pengguna Tiktok - Lestari, Vera Dewi; Kumalasari, Ana; Kasiami, Sri (Unitri Press, 2024)
This research aims to explain the utilization of social media by political parties and political actors towards the 2024 elections by using qualitative research methods. In this modern era, social media is starting to be recognized as a political campaign tool. This research explains how political parties and political actors utilize the Tiktok social media platform to build a good image, interact with voters and promote their political messages from the perspective of Tiktok users. By using qualitative data analysis, including observations and social media accounts. This research will provide knowledge about the strategy of utilizing social media as a medium for political campaigning and its impact on Indonesian democracy. The results of this study indicate that Tiktok users' perspectives on the use of social media as a campaign tool for the 2024 elections by political candidates show that they agree and feel effective. Tiktok users who are also voters also recommend several types of social media platforms that are also considered effective as campaign media for the 2024 Election, namely Instagram, Twitter and Facebook. Abstrak Penelitian ini bertujuan untuk menjelaskan pemanfaatan media sosial oleh partai politik dan aktor politik menuju Pemilu 2024 dengan menggunakan metode penelitian kualitatif. Di zaman yang serba modern ini, media sosial mulai dikenal sebagai alat kampanye politik. Penelitian ini menjelaskan bagaimana para partai politik dan aktor politik dalam memanfaatkan platform media sosial Tiktok untuk membangun citra baik, berinteraksi dengan pemilih dan mempromosikan pesan politik mereka dalam perspektif pengguna Tiktok. Dengan menggunakan analisis data kualitatif, termasuk observsi dan akun media sosial. Penelitian ini akan memberikan pengetahuan tentang strategi pemanfaatan media sosial sebagai media berkampanye politik serta dampaknya terhadap demokrasi Indonesia. Hasil penelitian ini menunjukkan bahwa perspektif pengguna Tiktok terhadap pemanfaatan media sosial sebagai alat kampanye Pemilu 2024 oleh kandidat politik menunjukkan rasa setuju dan merasa efektif. Pengguna Tiktok yang sekaligus sebagai pemilih juga merekomendasikan beberapa jenis platform media sosial yang juga dirasa efektif sebagai media kampanye Pemilu 2024 yaitu Instagram, Twitter dan Facebook.